1994
DOI: 10.1152/ajplung.1994.267.3.l256
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vasoactive intestinal peptide receptors on rat alveolar macrophages

Abstract: In view of the evidence that vasoactive intestinal peptide (VIP) may modulate acute inflammatory injury in the lung, we investigated the presence and characteristics of VIP receptors on alveolar macrophages (AMs). We examined the binding of monoiodinated [Tyr(125I)10]-labeled VIP (125I-VIP) to rat AMs (> 96% pure), obtained from Sprague-Dawley rats by bronchoalveolar lavage (BAL). At 23 degrees C, the interaction of 125I-VIP with AMs was rapid, reversible, saturable, and linearly proportional to the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The first report on VIP regulation of macrophage activation (Koff and Dunegan, 1985) clearly foresighted what became one of the main functions of VIP and PACAP as macrophage-deactivating factors (Ganea and Delgado, 2001a,b). Characterization of functional VIP and PACAP binding sites have been reported in both rat and mouse peritoneal macrophages (Segura et VIP IN IMMUNOMODULATION al., 1991;Calvo et al, 1994;Pozo et al, 1997a) and in rat alveolar macrophages (Sakakibara et al, 1994). The analysis of the binding data indicate two classes of binding sites, with the high-affinity site having a K d between 0.2 and 1.05 nM depending on the cell type.…”
Section: B Biochemical Pharmacological and Signaling Key Features mentioning
confidence: 91%
See 1 more Smart Citation
“…The first report on VIP regulation of macrophage activation (Koff and Dunegan, 1985) clearly foresighted what became one of the main functions of VIP and PACAP as macrophage-deactivating factors (Ganea and Delgado, 2001a,b). Characterization of functional VIP and PACAP binding sites have been reported in both rat and mouse peritoneal macrophages (Segura et VIP IN IMMUNOMODULATION al., 1991;Calvo et al, 1994;Pozo et al, 1997a) and in rat alveolar macrophages (Sakakibara et al, 1994). The analysis of the binding data indicate two classes of binding sites, with the high-affinity site having a K d between 0.2 and 1.05 nM depending on the cell type.…”
Section: B Biochemical Pharmacological and Signaling Key Features mentioning
confidence: 91%
“…The molecular weight of VPAC receptors in macrophages is particularly well characterized: 52 kDa in rat and mouse peritoneal macrophages (Pozo et al, 1997b) and 73 kDa in rat alveolar macrophages (Sakakibara et al, 1994). The 125 I-VIPreceptor complex's apparent molecular mass in rat splenocytes ranges from 52 to 55 kDa (Pozo et al, 2000).…”
Section: Vasoactive Intestinal Peptide Signalingmentioning
confidence: 99%
“…In the immune system, Guerrero et al ., 24 using binding techniques, described for the first time in 1981 the VPAC1 receptor in human peripheral blood lymphocytes. Later, it was reported in human monocytes, 25 murine lymphocytes, 26 and rat alveolar macrophages 27 . Moreover, gene expression of VPAC1 receptor has been demonstrated in T and B murine lymphocytes subpopulations from peripheral lymphoid organs, in single‐ and double‐positive CD4 + CD8 + murine thymocyte subsets and in peritoneal macrophages 12,28–30 .…”
Section: Vip–pacap Framework In Immunitymentioning
confidence: 95%
“…In the posterior pituitary, both the neural lobe (Hashimoto et al, 1996a) and the intermediate lobe (René et al, 1996) contain moderate concentrations of PAC1-R mRNA. In the pancreas, insulin-producing cells express both PAC1-R and VPAC2-R mRNAs (Usdin et al, 1994;Wei and Mojsov, 1996a,b;Filipsson et al, 1998a;Torii et al, 1998), whereas VPAC1-R mRNA is found only in the walls of Gottschall et al, 1990;Robberecht et al, 1991a;Shivers et al, 1991;Guijarro et al, 1992Guijarro et al, , 1995Huang et al, 1993;Nguyen et al, 1993;Bitar et al, 1994;Gagnon et Gottschall et al, 1990;Lam et al, 1990;Shivers et al, 1991;Bitar and Coy, 1993;Huang et al, 1993;Sakakibara et al, 1994;Sreedharan et al, 1995 Digestive system Colon ϩ ϩ ϩ Broyart et al, 1981;Prieto et al, 1981;Lam et al, 1990;Ekblad, 1999 blood vessels (Usdin et al, 1994). In the rat adrenal gland, type I PACAP binding sites have been characterized in medullary chromaffin cells and ganglion cells by cytoautoradiography (Shivers et al, 1991;Shioda et al, 2000) and immunocytochemistry .…”
Section: F Distribution Of Pituitary Adenylate Cyclaseactivating Polmentioning
confidence: 99%